Hydrothermal liquefaction of high- and low-lipid algae: Bio-crude oil chemistry. (15th November 2017) - Cheng, Feng; Cui, Zheng; Chen, Lin; Jarvis, Jacqueline; Paz, Neil; Schaub, Tanner; Nirmalakhandan, Nagamany; Brewer, Catherine E.
Highlights: Algal lipid and protein content affect the composition and upgrading of HTL oils. N. salina bio-crude oils contain more fatty acids, amides, and aliphatic molecules. G. sulphuraria bio-crude oils have more N- and O-heteroatom aromatic molecules. Bio-crude oils recovered with lower-polarity solvents are better for upgrading. Carbohydrates should be removed prior to HTL, but N removed by catalytic upgrading. Abstract: The bio-crude oil produced from hydrothermal liquefaction (HTL) of a high-protein microalgae useful for wastewater treatment, Galdieria sulphuraria, was comprehensively characterized, and compared to that of a high-lipid microalgae useful for biofuel production, Nannochloropsis salina . HTL was conducted in a batch reactor at temperatures of 310–350 °C and reaction times of 5–60 min. Characterization methods included high-resolution Fourier transform ion cyclotron resonance mass spectroscopy (FT-ICR MS), fatty acid methyl ester (FAME) analysis by gas chromatography mass spectroscopy (GC/MS), proton nuclear magnetic resonance spectroscopy ( 1 H NMR), and Fourier transform infrared spectroscopy (FT-IR). Milder reaction conditions favored bio-crude oil yield and quality for N. salina, while more severe conditions (350 °C) were needed for G. sulphuraria . N. salina -derived bio-crude oil contained mainly C14 -C18 fatty acid amides, while G. sulphuraria -derived bio-crude-oil had many N1-3 O0-2 hetero-atom compounds. FT-ICR MS showed that the aromaticity of hetero-compounds in N. salina bio-crude oil was higher due to N. salina 's higher carbohydrate content and the tendency of carbohydrate-derived molecules to condense at HTL conditions. FAME-GC/MS and 1 H-NMR results showed that stable fatty acid amides increased in G. sulphuraria bio-crude oil at higher temperatures as more protein-derived compounds combined with lipid-derived compounds. While N-containing and high molecular weight compounds are a concern for the upgrading of bio-crude oils obtained from high-protein algal biomass, removal of carbohydrates rather than removal of proteins as a pretreatment to HTL is recommended since carbohydrate-derived compounds are more likely to create highly aromatic hetero-compounds that are much more difficult to upgrade.